Association Between N363S and BclI Polymorphisms of the Glucocorticoid Receptor Gene (NR3C1) and Glucocorticoid Side Effects During Childhood Acute Lymphoblastic Leukemia Treatment - Meriç Kaymak Cihan; Halil Gürhan Karabulut; Nüket Yürür Kutlay; Hatice Ilgın Ruhi; Ajlan Tükün; Lale Olcay (Turkish Journal of Hematology, 2017)
Objective: Glucocorticoids (GCs) are the key drugs for the treatment of pediatric acute lymphoblastic leukemia (ALL). Herein, investigation of the relationship between the N363S and BclI polymorphisms of the GC receptor gene (NR3C1) and the side effects of GCs during pediatric ALL therapy was aimed. Materials and Methods: N363S and BclI polymorphisms were analyzed in 49 patients with ALL treated between 2000 and 2012. The control group consisted of 46 patients with benign disorders. The side effects of GCs noted during the induction and reinduction periods were evaluated retrospectively according to the National Cancer Institute's Common Terminology Criteria for Adverse Events, version 4.0. Results: The BclI allele and genotype frequencies were found similar in the two groups. No N363S polymorphism was detected in either of the groups. During induction, dyspepsia was found more frequently in the CG than in the CC (wild-type) genotype (36.4% vs. 5.3%, p=0.018) and depression symptoms more frequent in patients with the G allele (CG+GG) than the CC genotype (39.3% vs. 10.5%, p=0.031). During reinduction, Cushingoid changes, dyspepsia, and depression symptoms were more frequent in patients with the G allele (CG+GG) than in patients with the CC genotype (48.1% vs. 17.6%, p=0.041; 29.6% vs. 0.0%, p=0.016; 40.7% vs. 11.8%, p=0.040, respectively). Conclusion: In our study, patients with the BclI polymorphism were found to have developed more frequent side effects. We think that the BclI polymorphism should be considered while designing individualized therapies in childhood ALL.